2000
DOI: 10.1002/(sici)1521-3773(20000317)39:6<1045::aid-anie1045>3.0.co;2-q
|View full text |Cite
|
Sign up to set email alerts
|

A New Route to Fused Aromatic Compounds by Using a Palladium-Catalyzed Alkylation - Alkenylation Sequence

Abstract: Selective aromatic substitution is a long-standing goal in organic chemistry. [1] Recently, a new method involving a palladium-catalyzed process based on a sequential double aromatic substitution and an intermolecular Heck reaction leading to o,o'-disubstituted vinylarenes 2 was described (Scheme 1). [2] The potential of this strategy is truly remarkable since it allows the formation of three new carbon ± carbon bonds in a one-pot process.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
104
0

Year Published

2002
2002
2018
2018

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 254 publications
(106 citation statements)
references
References 2 publications
2
104
0
Order By: Relevance
“…Catellani and coworkers [17], and subsequently Lautens and coworkers [18], used a strained olefin as a directing scaffold for aromatic C-H functionalization [19,20]. Indeed, palladium-catalyzed ortho alkylation terminated by a cross-coupling such as the Mizoroki-Heck reaction was successfully achieved in a domino sequence through the use of norbornene as the directing group for the ortho-C-H activation step (Scheme 19.10) [21].…”
Section: Alkylation By the Catellani Reactionmentioning
confidence: 99%
“…Catellani and coworkers [17], and subsequently Lautens and coworkers [18], used a strained olefin as a directing scaffold for aromatic C-H functionalization [19,20]. Indeed, palladium-catalyzed ortho alkylation terminated by a cross-coupling such as the Mizoroki-Heck reaction was successfully achieved in a domino sequence through the use of norbornene as the directing group for the ortho-C-H activation step (Scheme 19.10) [21].…”
Section: Alkylation By the Catellani Reactionmentioning
confidence: 99%
“…Our group modified the reaction conditions and extended the methodology by using a difunctional acceptor (3) so that an intramolecular Heck reaction can follow the ortho alkylation leading to fused aromatic compounds 4 (Scheme 2) [4][5][6][7]. We initially demonstrated that numerous six-and seven-membered fused aromatic carbocycles (5) can be easily prepared using our optimized reaction conditions: iodoarene (1 equiv), Pd(OAc) 2 (10 mol %), tri-2-furylphosphine (22 mol %), Cs 2 CO 3 (2 equiv), norbornene (2 equiv), and bromoenoate (2 equiv) in acetonitrile at 85 °C for 12 h [4].…”
Section: Palladium-catalyzed Tandem Intermolecular Ortho Alkylation/imentioning
confidence: 99%
“…We initially demonstrated that numerous six-and seven-membered fused aromatic carbocycles (5) can be easily prepared using our optimized reaction conditions: iodoarene (1 equiv), Pd(OAc) 2 (10 mol %), tri-2-furylphosphine (22 mol %), Cs 2 CO 3 (2 equiv), norbornene (2 equiv), and bromoenoate (2 equiv) in acetonitrile at 85 °C for 12 h [4]. Various functional groups at different positions on the aryl iodide as well as a variety of Heck acceptors are tolerated [5].…”
Section: Palladium-catalyzed Tandem Intermolecular Ortho Alkylation/imentioning
confidence: 99%
“…69 Use of TFP in Tandem Palladium-catalyzed Synthetic Sequences. 82, 83 Oppolzer has extended his approach to double olefin insertion reactions. Liebeskind has systematically investigated the coupling of cyclobutenone electrophiles with unsaturated stannanes.…”
Section: CLmentioning
confidence: 99%